Clinical Practice Guideline for the Treatment of Percarditis - René Mick Cabrera Núñez; Lázaro de la Cruz Avilés (Revista Finlay)
Clinical practice guidelines aim at collecting and evaluating all the relevant evidence available on a particular topic. They are established to help doctors select the best possible treatment strategy for a specific patient, who suffers from a certain disease, not only taking into account the final result, but also weighing the risks and benefits of a diagnosis or concrete therapeutic procedure. This is a clinical practice guide for the treatment of acute pericarditis, defined as a syndrome caused by inflammation of the pericardium due to various etiologies. Its causal agents, clinical presentation, diagnostic methods and the management of acute pericarditis are described. It concludes with an evaluation guide, focused on the most important aspects to be met for proper patients´ treatment.